A relational account of visual short-term memory (VSTM). (November 2021) - Martin, Aimee; Becker, Stefanie I.
Abstract: Visual short-term memory (VSTM) is an important resource that allows temporarily storing visual information. Current theories posit that elementary features (e.g., red, green) are encoded and stored independently of each other in VSTM. However, they have difficulty explaining the similarity effect, that similar items can be remembered better than dissimilar items. In Experiment 1, we tested (N = 20) whether the similarity effect may be due to storing items in a context-dependent manner in VSTM (e.g., as the reddest/yellowest item). In line with a relational account of VSTM, we found that the similarity effect is not due to feature similarity, but to an enhanced sensitivity for detecting changes when the relative colour of a to-be-memorised item changes (e.g., from reddest to not-reddest item; than when an item underwent the same change but retained its relative colour; e.g., still reddest). Experiment 2 (N = 20) showed that VSTM load, as indexed by the CDA amplitude in the EEG, was smaller when the colours were ordered so that they all had the same relationship than when the same colours were out-of-order, requiring encoding different relative colours. With this, we report two new effects in VSTM – a relational detection advantage that describes an enhanced sensitivity to relative changes in change detection, and a relational CDA effect, which reflects that VSTM load, as indexed by the CDA, scales with the number of (different) relative features between the memory items. These findings support a relational account of VSTM and question the view that VSTM stores features such as colours independently of each other.